Clinical and Prognostic Role of 18F-FDG PET/CT in Pediatric Ewing Sarcoma. Issue 2 (March 2020) - Albano, Domenico; Dondi, Francesco; Schumacher, Richard Fabian; D'Ippolito, Carmelita; Porta, Fulvio; Giubbini, Raffaele; Bertagna, Francesco
Abstract : Ewing sarcoma (ES) is one of the most common pediatric solid tumors with aggressive behavior and unfavorable survival. In this study, we evaluated the diagnostic accuracy of baseline and restaging fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) scans and their possible prognostic role in pediatric ES. We evaluated 17 patients who underwent a total of 27 18F-FDG-PET/CT scans (10 for staging and 17 for restaging). The PET images were analyzed visually and semiquantitatively by measuring SUVmean, SUVmax, SUVlbm, SUVbsa, MTV, and TLG. Moreover, PET/CT results were compared with other conventional imaging (CI) results. Among 10 baseline PET/CT scan results, 9 were positive and 1 not valuable by interference; baseline PET/CT and CI were concordant in 7 cases and discordant in 2, with pulmonary micrometastases not detected by PET/CT. Among 17 restaging PET/CT scan results, 9 were positive and 8 negative; CI and restaging PET/CT were concordant in 9 cases and discordant in 8. Sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of restaging 18F-FDG-PET/CT were 73%, 83%, 89%, 62.5%, and 76%, respectively. After a median follow-up of 20 months, relapse/progression occurred in 8 patients and death in 5. A positive 18F-FDG-PET/CT at restaging was significantly associated with shorter overall survival compared with unremarkable PET/CT at the same timepoint, but not with progression-free survival. Instead, metabolic PET/CT features were not correlated with outcome. 18F-FDG-PET/CT showed a good diagnostic performance in pediatric ES; except for pulmonary micrometastases, PET/CT was better than CI at restaging. Only restaging PET/CT result was significantly correlated with overall survival.